2003
DOI: 10.1051/0004-6361:20021863
|View full text |Cite
|
Sign up to set email alerts
|

On the difference between the short and long gamma-ray bursts

Abstract: Abstract. We argue that the distributions of both the intrinsic fluence and the intrinsic duration of the γ-ray emission in gammaray bursts from the BATSE sample are well represented by log-normal distributions, in which the intrinsic dispersion is much larger than the cosmological time dilatation and redshift effects. We perform separate bivariate log-normal distribution fits to the BATSE short and long burst samples. The bivariate log-normal behaviour results in an ellipsoidal distribution, whose major axis … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 39 publications
4
88
0
1
Order By: Relevance
“…These are reasonable and not extreme values in view of model calculations for the energy release by neutrino-antineutrinoannihilation in case of post-merging BH accretion Janka et al 1999;Setiawan et al 2004). Provided a major fraction of the energy of the ultrarelativistic fireball gets converted to gamma-rays, our maximum isotropic equivalent energies are in good agreement with estimates based on a comparison of the energetics of short and long GRBs, suggesting an approximate fluence-duration proportionality (Balázs et al 2003). Since long bursts last typically about 50−100 times longer, a similar luminosity (e.g., Mao et al 1994; L short iso ∼ L long iso ∼ 10 51−52 erg s −1 ) implies an apparent energy which is around 10 51 erg for short bursts instead of ∼10 53 erg for long ones (Frail et al 1997).…”
Section: Discussionsupporting
confidence: 85%
“…These are reasonable and not extreme values in view of model calculations for the energy release by neutrino-antineutrinoannihilation in case of post-merging BH accretion Janka et al 1999;Setiawan et al 2004). Provided a major fraction of the energy of the ultrarelativistic fireball gets converted to gamma-rays, our maximum isotropic equivalent energies are in good agreement with estimates based on a comparison of the energetics of short and long GRBs, suggesting an approximate fluence-duration proportionality (Balázs et al 2003). Since long bursts last typically about 50−100 times longer, a similar luminosity (e.g., Mao et al 1994; L short iso ∼ L long iso ∼ 10 51−52 erg s −1 ) implies an apparent energy which is around 10 51 erg for short bursts instead of ∼10 53 erg for long ones (Frail et al 1997).…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, the redshift-convoluted 4-Dimensional (4D) rest-frame distribution can be well approximated as a linear translation of the observer-frame parameters to the restframe parameter space, keeping the shape of the distribution almost intact (e.g., Balazs et al 2003). This implies that the joint distribution of the intrinsic SGRB variables: the isotropic peak luminosity (Liso), the total isotropic emission (Eiso), the rest-frame time-integrated spectral peak energy (Ep,z) and the rest-frame duration (T90,z) might be indeed well described as a multivariate log-normal distribution.…”
Section: Model Constructionmentioning
confidence: 99%
“…For example, in the BATSE database, three subgroups (short, intermediate, and long GRBs) have been robustly identified (Horváth et al 2006;Chattopadhyay et al 2007, and references therein). The short and long subgroups are physically different phenomena (Balázs et al 2003). However, in contrast to this, it remains possible that the intermediate subgroup is not a true physically independent subgroup and it is present in the BATSE database because of e.g.…”
Section: Introductionmentioning
confidence: 96%
“…We proceed in an identical way to the successful statistical analysis completed for the BATSE catalog (Horváth 1998) leading to the discovery of the third subgroup (Mukherjee et al 1998;Bagoly et al 1998;Horvath 1999;Hakkila et al 2000;Rajaniemi & Mähönen 2002;Horváth 2002Horváth , 2003Balázs et al 2003;Horváth et al 2006;Chattopadhyay et al 2007). A statistical study of the Swift database -using the maximum likelihood method -has already shown evidence of a third subgroup (Horváth et al 2008).…”
Section: Introductionmentioning
confidence: 97%